Citizenship organizational behavior ability to increase the effect of organizational climate, work motivation, and organizational justice on employee performance - Purwantoro, Handik; Bagyo, Yupono (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
This research aim is to examine the effect of Organization Climate, Work Motivation and Organizational Justice on Employee Performance mediated by Organizational Citizenship Behavior (OCB). The population are 50 Ursa Mayora Consultants. The data is collected by questionnaires and analyzed by path analysis. The test results prove that Organizational Climate, Work Motivation and Organizational Justice significantly affect on Employee Performance with OCB as mediation variable at CV. Ursa Mayora Consultant.